Neutralität nach "Schweizer Muster"? Österreichische Völkerrechtslehre zur immerwährenden Neutralität, 1955-1989 - Schreiner, Julia (Studien zur Geschichte des Völkerrechts, 2018)
"Permanent neutrality - a chance or more a burden for a young nation? In 1955 Austria gained back its sovereignty with signing the State Treaty of Vienna. Before that, Austria took over the obligation of becoming a permanent neutral state in the Moscow Memorandum. This study focuses on the efforts of Austrian politics, science and people to position the country in Europe and in the United Nations within the framework of the Cold War. The analysis shows how the semantics and the functions of the permanent neutrality have changed from 1955 to 1989 and how the Austrian citizens have contemplated the neutrality of their state. Moreover the study explores the interdependency between political developments and scientific research and, as a consequence of that, the role neutrality played on a political level. The examination reveals the various definitions of neutrality and points out the significance it still has today. "